Network meta-analysis of short-term effects of different strategies in the conservative treatment of AIS - Kepeng Li; Jun Miao; Jingan Zhang (European Journal of Medical Research, 2021)
Abstract Purpose To evaluate the short-term effects of different conservative treatments on in adolescent idiopathic scoliosis. Methods By searching the relevant literature of adolescent idiopathic scoliosis, the curative effects of the three regimens of bracing therapy combined with scoliosis-specific exercises, simple treatment with brace and simple scoliosis-specific exercises were compared. Review manager 5.3, Stata MP16 and Network software packages were used for Reticular Meta-analysis of Cobb’s angles before and after treatment. Results A total of 364 patients were included in four clinical studies. Reticular meta-analysis showed that the short-term effect of bracing treatment combined with scoliosis-specific exercises was better than that of treatment with brace and scoliosis-specific exercises, with effects of 2.71(95% CI 0.83–4.58) and 3.67(95% CI 1.21–6.14), respectively. There was no statistical difference between simple bracing therapy and scoliosis-specific exercises. Conclusion Among the three common conservative treatments of adolescent idiopathic scoliosis, the short-term effect of bracing treatment combined with scoliosis-specific exercises is better than that of bracing treatment or scoliosis-specific exercises.